2006
DOI: 10.1111/j.1365-2133.1995.tb02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential liver biopsies during long-term methotrexate treatment for psoriasis: a reappraisal

Abstract: One hundred and eighty-two liver biopsies were performed over a K)-year period on patients receiving long-term, low-dose, once weekly oral melhotrexate (MTX) lor severe psoriasis. Eorty-nine patients had two or more biopsies during continued treatment and formed the study population for our analysis. The first and last biopsies were compared to determine progression of any histological abnormalities. Liver bit)psies were assessed without knowledge ofthe MTX dose and allocated to one of five groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 16 publications
3
59
1
4
Order By: Relevance
“…The test is not organ specifi c, and it is not a marker of fi brosis but of fi brogenesis. The study supported the view [4] that, as long as PIIINP is consistently normal in serial investigations, there is only a minimal risk of development of substantial liver fi brosis.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…The test is not organ specifi c, and it is not a marker of fi brosis but of fi brogenesis. The study supported the view [4] that, as long as PIIINP is consistently normal in serial investigations, there is only a minimal risk of development of substantial liver fi brosis.…”
supporting
confidence: 75%
“…All guidelines have dealt specifi cally with the question of how to monitor hepatotoxicity and recommended the performance of liver biopsies, at least when the cumulative dose reached 1.5 g. Concern about the toxicity arose from a number of studies showing high frequencies of liver fi brosis (up to 50%) and cirrhosis (up to 26%) on long-term MTX treatment [2] . Within recent years, it has however been suggested that it is time to reconsider the use of liver biopsies in these patients [3][4][5][6] . Two main reasons for a reappraisal have been brought forward, the appearance of new noninvasive tests [3,4] and reports on the less frequent appearance of MTX-induced fi brosis and cirrhosis [5,6] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver fibrosis is the main disadvantage, although studies [1][2][3][4] vary on the prevalence of methotrexate-induced liver injury in patients with psoriasis. Frequent evaluation of liver enzyme levels and procollagen III peptide (PIIINP) levels 5,6 as well as periodic liver biopsies have been recommended during therapy.…”
Section: Invited Commentary Page 862mentioning
confidence: 98%
“…These conditions increase the risk of liver disease and adverse effects related to the liver biopsy procedure. 4 In addition, the histologic accuracy of a liver biopsy may be affected by sampling error, pathologist inconsistency in observations, and discontinuous and semiquantitative histologic scoring systems.…”
Section: Invited Commentary Page 862mentioning
confidence: 99%